Pengaruh Literasi Keuangan, Kontrol Diri, Dan Lingkungan Teman Sebaya Terhadap Perilaku Konsumtif Mahasiswa Ekonomi Universitas Muhammadiyah Ponorogo Pengguna Aplikasi Belanja Online - Zulfa Nur Aini; Titi Rapini; Riawan Riawan (The Academy Of Management and Business, 2023)
The purpose of this study is to analyze "The Influence of Financial Literacy, Self-Control, and Peer Environment on Consumptive Behavior of Economics Students at Muhammadiyah University Ponorogo Users of Online Shopping Applications". The method used in this research is the quantitative method. The source of data used in this research is primary data. The results of the study show that financial literacy, self-control, and peer environment have a significant positive effect on consumptive behavior. While the results of the simultaneous test stated that financial literacy, self-control, and peer environment had a significant positive effect on consumptive behavior simultaneously.